The planning of library and documentation services - Penna, Carlos Victor; Sewell, Philip Hooper; Liebaers, Herman (Paris : Unesco, 1970)
The provision of effective library and documentation services to promote education and research at different levels and economic and social endeavour of various kinds requires that they be organised within an integrated system which is itself conceived in relation to and as a part of national plans for economic and social development
First ed. published in 1967 under title: Planning library services.
UNESCO manual for Libraries
Includes bibliographical references.
obn 21/01/2018
Loans
Keywords: Library planning; Library planning - documentation